Protocol for a single-centre, parallel-arm, randomised controlled superiority trial evaluating the effects of transcatheter arterial embolisation of abnormal knee neovasculature on pain, function and quality of life in people with knee osteoarthritis. Issue 5 (29th May 2017) - Landers, Steve; Hely, Andrew; Harrison, Benjamin; Maister, Nick; Hely, Rachael; Lane, Stephen E; Gill, Stephen D; Page, Richard S
Abstract : Introduction: Symptomatic knee osteoarthritis (OA) is common. Advanced knee OA is successfully treated with joint replacement surgery, but effectively managing mild to moderate knee OA can be difficult. Angiogenesis increases with OA and might contribute to pain and structural damage. Modifying angiogenesis is a potential treatment pathway for OA. The aim of the current study is to determine whether transcatheter arterial embolisation of abnormal neovasculature arising from the genicular arterial branches improves knee pain, physical function and quality of life in people with mild to moderate symptomatic knee OA. Methods and analysis: The study is a single centre, parallel-arm, double-blinded (participant and assessor), randomised controlled superiority trial with 1:1 random block allocation. Eligible participants have mild to moderate symptomatic knee OA and will be randomly assigned to receive either embolisation of aberrant knee neovasculature of genicular arterial branches or a placebo intervention. Outcome measures will be collected prior to the intervention and again 1, 6 and 12 months postintervention. The primary outcome is change in knee pain between baseline and 12 month assessment as measured by the Knee Injury and Osteoarthritis Outcome Score (KOOS). Secondary outcomes include change in self-reported physical function (KOOS), self-reported quality of life (KOOS, EuroQol: EQ-5D-5L), self-reported knee joint stiffness (KOOS), self-reported global change, 6 min walk test performance, and 30 s chair-stand test performance. Intention-to-treat analysis will be performed including all participants as randomised. To detect a mean between group difference in change pain of 20% at the one year reassessment with a two-sided significance level of α=0.05 and power of 80% using a two-sample t-test, we require 29 participants per arm which allows for 20% of participants to drop out. Ethics and dissemination: Barwon Health Human Research Ethics Committee, 30 May 2016, (ref:15/101). Study results will be disseminated via peer-reviewed publications and conference presentations. Trial registration number: Universal trial number U1111-1183-8503, Australian New Zealand Clinical Trials Registry, ACTRN12616001184460, approved 29 August 2016.